Molecular Dynamics Simulations of Plasma–Antifolate Drug Synergy in Cancer Therapy - Yanxiong Niu; Tong Zhao; Xiaolong Wang; Ying Sun; Yuantao Zhang (Biomolecules, 2025)
Reactive oxygen species (ROS) generated by cold atmospheric plasma (CAP) cause irreversible damage to cancer cell DNA, RNA, mitochondria, and antioxidant defense systems, leading to apoptosis. Plasma-induced disruption of the antioxidant defense system of cancer cells by cystine uptake via xC− antiporter has been widely studied, while folate uptake by cancer cells via high expression of hSLC19A1, which generates Nicotinamide Adenine Dinucleotide Phosphate (NADPH) via one-carbon metabolism, is also an important component of the antioxidant defense mechanism of cancer cells. Disrupting folate transport in cancer cells is an important potential pathway for synergizing with pemetrexed (PMX) to induce apoptosis in cancer cells, which is of great research value. In this paper, classical molecular dynamics simulations were employed to study the effect of plasma oxidation of hSLC19A1 on the uptake of 5-Methyltetrahydrofolate (5-MTHF), which is the predominant dietary and circulatory folate, and the antifolate chemotherapeutic agent PMX by cancer cells. The results showed that the channel radius of hSLC19A1 for transporting 5MTHF after oxidation became narrower and the conformation tended to be closed, which was unfavorable for the transport of 5-MTHF; hydrogen bonding and hydrophobic interactions between hSLC19A1 and 5-MTHF decreased, the predicted docking affinity decreased, and the binding energy decreased from −28.023 kcal/mol to −16.866 kcal/mol, while that with PMX was stable around −28 kcal/mol, suggesting that the oxidative modification reduced the binding capacity of hSLC19A1 and 5-MTHF while barely affecting the transport of PMX, which contributed to weakening the antioxidant defense system of cancer cells and synergizing with PMX to induce apoptosis in cancer cells. Our simulations provide theoretical insights for CAP-induced apoptosis in cancer cells at the microscopic level and help promote the further development of cold atmospheric plasma in the field of cancer therapy.